Harmonization strategy of the spatial information infrastructure of Ukraine with INSPIRE. system approach - Chabaniuk, V.; Dyshlyk, O. (Land Management, Cadastre and Land Monitoring, 2024)
Van Gigch's system approach was applied to consider the option of systemic harmonization of the National Spatial Information Infrastructure of Ukraine (NSII) with INSPIRE. The article focuses on its most important part - the strategy of harmonization or, more specifically, strategic harmonization. The proposed strategic harmonization is suitable for practical implementation. For this purpose, NSII is understood as an extension of National Spatial Data Infrastructure (NSDI), and NSII and INSPIRE are represented by general systems (GS), whose practical feasibility is achieved by exemplification/interpretation by spatial information systems (SpIS) and certain their extensions - SpISb. The main attention is paid to the relation between the NSII and INSPIRE, with an emphasis on the harmonization relation. Possible alternatives to the problems or their solutions are not considered. In particular, the likely recent shift of interest from NSDI/NSII/INSPIRE to IGIF (Integrated Geospatial Information Framework) is not considered. This is possible because van Gigch's system approach used allows scaling, in this case - upwards, with the addition of higher levels of the hierarchy such as IGIF to the consideration.It is shown that, in the context of harmonization with INSPIRE, it is necessary to examine the harmonization of GS on at least three epistemological levels. GS corresponding to these levels can be called: strategic, tactical and operational. The GS for harmonization with INSPIRE can be represented by an integrated hierarchy or a unification of three GS components of these three levels. In the case of unification, each component of the collective agreement can be considered separately, but the context of harmonization must be mandatory. In particular, in strategic harmonization, it is mandatory to define its hierarchical relations with the "corresponding" tactical harmonization.Two main results were obtained in the article: 1) scientific - the structure of the phenomenon "harmonization of Ukrainian SII with INSPIRE" was defined, 2) practical - it was proved that the specified phenomenon is adequately represented by the GS and the corresponding SpISb.
Keywords: Spatial Information Infrastructure (SII) of Ukraine (NSII); Spatial/Geospatial Data Infrastructure of Ukraine (NSDI/NGDI); strategic harmonization; methodologies of harmonization; system approaches of van Gigch and G. Klir